Respuesta :

caylus
Hello,

(x-(-1+4i))(x-(-1-4i))=((x+1)-4i)((x+1+4i)
=((x+1)²+16
=x²+2x+17

Answer:

[tex]x^2 + 2x + 17[/tex]

Step-by-step explanation:

Since, a quadratic equation having roots [tex]\alpha[/tex] and [tex]\beta[/tex] is,

[tex]x^2 - (\alpha+\beta)x + \alpha.\beta[/tex]

Here,

[tex]\alpha = -1 + 4i[/tex]

[tex]\beta = -1 - 4i[/tex]

Hence, the required quadratic equation,

[tex]x^2 - (-1+4i- 1 - 4i)x + (-1+4i)(-1-4i)[/tex]

[tex]x^2 + 2x + ( (-1)^2 - (4i)^2)[/tex]   ( ∵ a² - b² = (a+b)(a-b) )

[tex]x^2 + 2x + (1 + 16)[/tex]   ( ∵ i² = -1 )

[tex]x^2 + 2x + 17[/tex]